Implementation of Digital Literacy Movement in Students of Sekolah Dasar Negeri 09 North Pontianak - Muhammad Khoirul Farizal; Vidya Setyaningrum (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
The digital literacy movement helps students to develop critical and analytical thinking skills in evaluating digital information, so that they can distinguish true and useful information from misleading or harmful information. This study aims to explore the implementation of digital literacy at SDN 09 North Pontianak, identify challenges and supporting factors in the learning process. Using a qualitative approach and descriptive design, this study collected data through observation, interviews with the principal, teachers and students, and documentation. The findings show that although the school has shown commitment by providing infrastructure such as Chromebooks and projectors, challenges such as limited access to technology at home and students' fear and hesitation in using digital devices remain. Learning strategies involving collaboration between low- and high-ability students were implemented to improve digital literacy skills. This study concludes that the success of digital literacy at SDN 09 North Pontianak relies heavily on support from parents and the community, as well as a gradual approach to the introduction of technology. With the right support, schools can prepare students to face the challenges and opportunities of the digital era.